Rheumatology Clinic Staff Needs: Barriers and Strategies to Addressing High Blood Pressure and Smoking Risk. Issue 7 (12th October 2022) - Tong, Michelle; Gilmore-Bykovskyi, Andrea; Block, Laura; Ramly, Edmond; White, Douglas W.; Messina, Monica L.; Bartels, Christie M.
Abstract : Objective: Patients with rheumatologic conditions are at elevated risk of cardiovascular disease (CVD) due to inflammatory and traditional risk factors, such as high blood pressure (BP) and smoking. However, rheumatology clinics rarely address traditional risk factors, although they are routinely assessed and modifiable in primary care. The present study sought to (1) characterize rheumatology clinic staff's work process for addressing high BP and smoking and (2) identify barriers and strategies for effective management of these risk factors. Methods: We conducted 7 focus groups with medical assistants, nurses, and scheduling staff from 4 adult rheumatology clinics across 2 health systems (BP focus groups, n = 23; smoking, n = 20). Transcripts were analyzed using thematic analysis to elucidate barriers and strategies. Results: We found 3 clinic work processes for the management of high BP and smoking risk: (1) risk identification, (2) follow-up within the clinic, and (3) follow-up with primary care and community resources. Within these processes, we identified barriers and strategies grouped into themes: (1) time, (2) clinic workflows, (3) technology and resources, (4) staff's attitudes and knowledge, and (5) staff's perceptions of patients. The most pervasive barriers were (1) no structured system for follow-up and (2) staff confidence and skill in initiating conversations about health-related behavior change. Conclusions: Our study identified generalizable gaps in rheumatology staff's work processes and competencies for addressing high BP and smoking in patients. Future efforts to support staff needs should target (1) systems for follow-up within and outside the clinic and (2) conversation support tools.